Functional regionalization of the differentiating cerebellar Purkinje cell population occurs in an activity-dependent manner - Alessandro Dorigo; Komali Valishetti; Florian Hetsch; Florian Hetsch; Hideaki Matsui; Hideaki Matsui; Jochen C. Meier; Kazuhiko Namikawa; Reinhard W. Köster (Frontiers in Molecular Neuroscience, 2023)
IntroductionThe cerebellum is organized into functional regions each dedicated to process different motor or sensory inputs for controlling different locomotor behaviors. This functional regionalization is prominent in the evolutionary conserved single-cell layered Purkinje cell (PC) population. Fragmented gene expression domains suggest a genetic organization of PC layer regionalization during cerebellum development. However, the establishment of such functionally specific domains during PC differentiation remained elusive.Methods and resultsWe show the progressive emergence of functional regionalization of PCs from broad responses to spatially restricted regions in zebrafish by means of in vivo Ca2+-imaging during stereotypic locomotive behavior. Moreover, we reveal that formation of new dendritic spines during cerebellar development using in vivo imaging parallels the time course of functional domain development. Pharmacological as well as cell-type specific optogenetic inhibition of PC neuronal activity results in reduced PC dendritic spine density and an altered stagnant pattern of functional domain formation in the PC layer.DiscussionHence, our study suggests that functional regionalization of the PC layer is driven by physiological activity of maturing PCs themselves.